DEVELOPMENT OF A BLENDED LEARNING MODEL TO INCREASE CADET LEARNING MOTIVATION AT MAKASSAR AVIATION POLYTECHNIC - Irfan; ABD.GANI, HAMSU; Nur, Hasanah (Jurnal Vokasi Keteknikan, 2023)
The model can be used as an alternative learning model that can meet learning development and improve cadet competence. The type of research used is Research and Development (R & D), the development of learning models in this study is a combination of models (1) Plomp (1997), (2) Dick & Carey (2005), and Joyce et al (2004). The Plomp model was used for the research and development phase of the model, Dick & Carey for instructional design, and Joyce et al for the contents of the model. The instrument used is valid, where the criteria used have an adequate degree of validity if the Va value is in the minimum valid category, so it is suitable for use while the level of reliability of the instrument using the percentage of agreements (PA) with instrument sheet criteria is said to be reliable if the PA value ≥ 0.70. The results of this study show that the development of the blended learning model developed meets valid, practical and effective criteria to increase cadet learning motivation in learning both in individual and group discussion activities.